Duodenal microbiome in patients with or without Helicobacter pylori infection. Issue 6 (8th September 2020) - Suárez‐Jaramillo, Andrés; Baldeón, Manuel E.; Prado, Belén; Fornasini, Marco; Cohen, Henry; Flores, Nancy; Salvador, Iván; Cargua, Oswaldo; Realpe, José; Cárdenas, Paul A.
Abstract: Background: Intestinal microbiota are recognized as an organ with important physiological functions whose alterations have been associated with common diseases including inflammatory intestinal conditions, malnutrition, type‐2 diabetes, and cardiovascular diseases. The composition and function of the microbiota in the distal part of the intestine has been mainly described, while there is limited information on the small intestine microbiota. The objective of the present study was to describe the duodenal microbiome in individuals with dyspepsia in the presence or absence of Helicobacter pylori gastric infection. Materials and Methods: Thirty‐eight biopsies from the proximal duodenum of uninfected and 37 from H pylori ‐infected individuals were analyzed. Microbiota composition was assessed by PCR amplification and sequencing of 16S rRNA and ITS genes; sequences were analyzed with QIIME2. Results and Conclusions: At the phyla level, Proteobacteria, Bacteroidetes, Firmicutes, Actinobacteria, and Fusobacteria were predominant in the mucosal associated duodenal microbiota (MAM); at the genera level, we observed the predominance of Ralstonia, Streptococcus, Pseudomonas, Haemophilus, Herbaspirillum, Neisseria, and Veillonella . Microbiota α‐diversity was higher in H pylori ‐infected individuals than in non‐infected ones. In terms of β‐diversity metrics, there was a statistically significant difference between groups. Also, relative abundance of Haemophilus, Neisseria, Prevotella pallens, Prevotella 7, and Streptococcus was greater in H pylori ‐infected patients. In infected patients, several types of H pylori were present in duodenal MAM. Finally, the majority of duodenal samples had fungi sequences; the most common taxa observed were Recurvomyces followed by Ascomycota and Basidiomycota.